Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils

Plant-pathogen interactions: microRNA-mediated trans-kingdom gene regulation in fungi and their host plants - Mathur, Monika; Nair, Aswathy; Kadoo, Narendra (Genomics, 2020)
MicroRNAs (miRNAs) have been prevalently studied in plants, animals, and viruses. However, recent studies show evidences of miRNA-like RNAs (milRNAs) in fungi as well. It is known that after successful infection, pathogens hijack the host machinery and use it for their own growth and multiplication. Alternatively, resistant plants can overcome the pathogen attack by a variety of mechanisms. Based on this prior knowledge, we computationally predicted milRNAs from 13 fungi, and identified their targets in transcriptomes of the respective fungi as well as their host plants. The expressions of the milRNAs and targets were confirmed using qRT-PCR. We found that plant miRNAs targeted fungal virulence genes, while fungal milRNAs targeted plant resistance genes; corroborating miRNA-mediated trans-kingdom gene regulation and the roles of miRNAs in plantpathogen interactions. Transgenic plants with miRNAs targeting fungal virulence genes, or anti-sense of fungal milRNAs, would be expected to be highly resistant to the fungal pathogens.
Keywords: Disease resistance; Fungal miRNAs; qRT-PCR; Resistance genes; Target prediction; Virulence genes